DIFFERENT CERVICAL LAMINOPLASTY TECHNIQUES - UPDATE AND SYSTEMATIC REVIEW - FRANCISCO ALVES DE ARAÚJO JÚNIOR; JURANDIR MARCODES RIBAS FILHO; OSVALDO MALAFAIA; ALUÍZIO AUGUSTO ARANTES JÚNIOR; GUILHERME HENRIQUE WEILER CECCATO; PEDRO HELO DOS SANTOS NETO (Coluna/Columna)
ABSTRACT This review aims to update the cervical laminoplasty techniques described in the literature and perform a systematic review of the open-door (ODL) and French-door (FDL) laminoplasties. A literature review was conducted on the Pubmed and Scielo platforms. This study was separated into two phases. The first section reviewed the laminoplasty techniques described in the literature. In this phase, a literature review was carried out using the descriptor “cervical laminoplasty”, employing “clinical trial”, “meta-analysis”, “review,” and “systematic review” as filters. The second section was a systematic review of the two most-studied techniques, the open-door and French-door laminoplasties. In this phase, a review was carried out using the descriptors “cervical laminoplasty”, “open-door” and “French-door” or “double-door”, employing “meta-analysis” and “review” as filters. In both phases, no limits were defined on the period. The first laminoplasty was described in 1973 and, since then, there have been, at least, six more techniques described that involve opening the spinal canal. Other studies report slight modifications in the type of spine access or details related to the osteotomy technique. Five systematic reviews were performed comparing the ODL and FDL. Only two of them analyzed common variables, and their results were divergent. Both ODL and FDL achieve favorable clinical and radiological results for the patient, and it is not yet possible to say whether one is better than the other. Level of Evidence II; Therapeutic Studies.